Tadeusz Marian Kobusiewicz (1905–1979) – wybitny profesor weterynarii, kapitan WP, założyciel Zakładu Pryszczycy Państwowego Instytutu Weterynaryjnego - Stulczewski, Jarosław (Biuletyn Szadkowski, 2012)
Tadeusz Marian Kobusiewicz - eminent professor in veterinary medicine, captain of the Polish Army, was bom in Szadek. He eamed doctor's degree in Warsaw in 1934, then served intemship in Great Britain in 1939, and in Pasteur Institute in Paris in 1945. In 1951 he became head of the Institute for Research on Foot-and-Mouth Desease in Gorzów Welkopolski, and in 1953 set up in Zduńska Wola a Foot-and-Mouth Desease Section of the Veterinary Medicine Institute. He was a dedicated social worker, actively engaged in sports promotion, chairman of the Łódź Section of Veterinary Doctors and Technicians Association, and councillor in Zduńska Wola. T. M. Kobusiewicz was the first Polish veterinary doctor to successively immunize against tenatus all horses in the Polish Army. He was the best in Poland specialist on the foot-and-mouth desease, who provided scientific foundations for prevention and cure of this desease. In recognition of his merits he was awarded I Class Order of the Banner of Labour. Died in 1979. One of the streets in Zduńska Wola was given his name.